Nanometric assembly of functional terpyridyl complexes on transparent and conductive oxide substrates: structure, properties, and applications - Mondal, Prakash Chandra; Zharnikov, Michael (Accounts of chemical research, 2017)
CONSPECTUSOver the last few decades, molecular assemblies on solid substrates have become increasingly popular, challenging the traditional systems and materials in terms of better control over molecular structure and function at the nanoscale. A variety of such assemblies with high complexity and adjustable properties was generated on the basis of organic, inorganic, organometallic, polymeric, and biomolecular building blocks. Particular versatile elements in this context are terpyridyls due to their wide design flexibility, ease of functionalization, and ability to coordinate to a broad variety of transition-metal ions without forming diastereoisomers, which facilitates tuning of their optical and electronic properties. Specifically, metal-terpyridyl complexes are worthy building blocks for generating optoelectronically active assemblies on technologically relevant transparent and conductive oxide substrates.In this context, the present Account summarizes our recent results on the preparation, characterization, and applications of nanometric (2-10 nm) surface-confined molecular assemblies of Cu2+, Fe2+, Ru2+, and Os2+-terpyridyl complexes on SiOx-based substrates (glass, quartz, silicon, and ITO-coated glass). These assemblies rely on covalent bond formation between the iodo-/chloro-terminated functionalized SiOx substrates and the pendant group (mostly pyridyl) hosted on the terpyridyl complexes. Such an anchoring provides excellent thermal, temporal, radiative, and electrochemical stability to the assemblies as needed for technological applications. The functional, covalently assembled monolayers were extended to fabricate molecular dyads (bilayers), triads (trilayers), and oligomers by an established layer-by-layer procedure using suitable metallolinkers such as Cu2+, Ag+, and Pd2+. The chemical, optical, and electrochemical properties of these assemblies could be precisely adjusted by selection of proper metal-terpyridyl complexes and/or metallolinkers, so that the resulting systems served, relying on the specific design, as sensors, catalysts, molecular logic gates, and photochromic devices. For instance, a Cu-terpyridyl-based assembly on a glass substrate showed “turn on” detection of ascorbic acid. In another example, heterometallic molecular triads were exposed to redox-active NO+ for selective oxidation of the metal ions, and the optical readout was utilized for configuring multiple-input-based molecular logic gates. Furthermore, bias-driven (+0.6 to +1.6 V vs Ag/AgCl) optical properties of the heteroleptic Ru2+/Os2+-terpyridyl monolayers were modulated and “read out” by spectro-electrochemical techniques demonstrating high charge/information density (3-4 × 1014 electrons/cm2). Moreover, the manipulation of the M2+/3+ (M = Fe, Ru, and Os) redox wave in the assembly provided the possibility to create mixed-valence redox-states paving the way toward the fabrication of “multi-bit” memory systems. We truly believe that due to these intriguing characteristics and excellent stability, terpyridyl-based molecular assemblies have the potential to become a versatile platform for the next generation of smart optoelectronic devices.
Gesehen am 26.04.2018